Handbook for coffee cultivators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Coffee growing by H R Cambrony 1992 (originally in French under the title Le Cafeier) 119pp ISBN 0 333 54451 X Pbk in the CTA/Macmillan series The Tropical Agriculturist Macmillan Publishers Ltd, 4 Little Essex Street London WC2, UK Also avail